PERAN NOTARIS DALAM PROSES ALIH KREDIT PEMILIKAN RUMAH SUBSIDI - Dian Hanani; Putu Samawati Saleh (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2023)
This research aims to find out the role of the Notary in the process of transferring subsidized home ownership credit (KPR in Indonesia) at the main branch of PT.BTN Palembang. This research is a type of normative research using library research material collection techniques. The background to this writing is that in practice there is often a transfer of subsidized home ownership credit (KPR) carried out by debtors who have been placed in subsidized housing for less than 5 (five) years. This is contrary to Article 29 paragraph (4) letter e Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 35 Years 2021 concerning ease and assistance in obtaining housing for low-income people. The role of the Notary in this case is to make an authentic deed relating to the process of transferring subsidized home ownership credit (KPR) to the main branch of PT BTN Palembang. The deeds required in the credit transfer process are a statement of transfer of rights, a Deed of Sale and Purchase Agreement, a power of attorney to pay off the installments, and a power of attorney to take the house certificate. In this credit transfer process, in carrying out his position, the Notary must pay attention to the principle of balance.